BRIGHT Coaching: A Randomized Controlled Trial on the Effectiveness of a Developmental Coach System to Empower Families of Children With Emerging Developmental Delay - Majnemer, Annette; O'Donnell, Maureen; Ogourtsova, Tatiana; Kasaai, Bahar; Ballantyne, Marilyn; Cohen, Eyal; Collet, Jean-Paul; Dewan, Tammie; Elsabbagh, Mayada; Hanlon-Dearman, Ana; Filliter, Jillian Helen; Lach, Lucyna; et al. (Frontiers in Pediatrics, 2019)
Background: In preschool-aged children with, or at elevated risk for, developmental disabilities, challenges and needs arise from vulnerabilities linked to critical and newly emerging cognitive, speech, motor, behavioural and social skills. For families, this can be a stressful period as they witness the gradual unfolding of their child’s differences and await to receive care. Nationally and internationally, service delivery models during this critical period are not standardised nor are they nimble or sufficient enough, leading to long wait times, service gaps and duplication. Given these struggles, there is a need to examine whether ‘health coaching’, a structured educational program that is deliverable by different and more accessible means, can be effective in empowering families, by delivering information, providing social supports, and decreasing the demands on the overwhelmed health and developmental services. The primary objective is to evaluate the feasibility and the effectiveness of a coaching intervention (in comparison to usual and locally available care), for parents of children with emerging developmental delays. Method/Design: A multi-centred pragmatic randomised controlled trial design will be used. Families will be recruited from a representative sample of those awaiting publicly-funded regional child health services for children with developmental delays in four Canadian provinces. The target sample size is 392 families with children aged 1.5 to 4.5 years at recruitment date. Families will be randomly assigned to receive either the BRIGHT Coaching intervention (coach supported, hard-copy and online self-managed educational resources: 14 sessions, 2 sessions every 4 weeks for 6-9 months) or usual care that is locally available. In addition to the feasibility and acceptability measures, outcomes related to family empowerment, parental satisfaction and efficacy with caregiver competency will be evaluated at baseline, post-treatment (8 months), and follow-up (12 months). Discussion: This manuscript presents the background information, design, description of the interventions and of the protocol for the randomised controlled trial on the effectiveness of BRIGHT Coaching intervention for families of children with emerging developmental delays. Trial registration: ClinicalTrials.gov, U.S. National Library of Medicine, National Institutes of Health #NCT03880383, 03/15/2019. Retrospectively registered.